Belarus Regional Development Policy Notes : Spatial Dimension of Structural Change - World Bank (Washington, DC, 2015)
This report focuses on two competing forces: the Soviet industrial legacy and emerging economic activities, mostly in the form of micro, small, and medium enterprises (MSMEs). The large, often vertically integrated, state-owned enterprises (SOEs) that are part of the Soviet legacy still have a considerable role in many industries and indeed dominate the economies of certain rayons and even oblasts. This report shows that because MSMEs generate new jobs and output without draining state resources, it is important to encourage their creation and open opportunities for existing companies to expand, particularly micro and small enterprises. This growth is geographically uneven, with a tendency of economic activities to gravitate to industrialized centers. The report revisits the policy debates on how to improve regional economies and their welfare.